Microzonation of Zeytinburnu region with respect to soil amplification:: A case study - Kilic, Havvanur; Oezener, Pelin Tohumcu; Ansal, Atilla; Yildirim, Mustafa; Oezaydin, Kutay; Adatepe, Senol (ELSEVIER SCIENCE BV, 2006)
A microzonation study is performed as a part of the Zeytinburnu Pilot Project within the framework of the Earthquake Master Plan for Istanbul to determine the effects of local soil conditions on the earthquake forces that will act on structures. For this purpose, detailed geological and geotechnical studies are conducted at the site, a geological map which demonstrates the local geological features of the site is prepared, and the site is classified with respect to the dynamic behaviour based on the data gathered from the soil borings. In order to investigate the effects of local soil conditions on the dynamic behaviour, site response analyses are performed with the computer code EERA by utilizing the findings of field and laboratory investigations. The behaviour of the region during a probable earthquake is investigated through one dimensional response analyses and microzonation maps are prepared with respect to ground shaking intensity in accordance with the new microzonation manual [Ansal, A., Laue, J., Buchheister, J., Erdik, M., Springman, S., Studer, J., and Koksal, D., 2004. Site characterization and site amplification for a seismic microzonation study in Turkey 11th Int. Conference on Soil Dynamics and Earthquake Engineering and 3rd Earthquake Geotechnical Engineering, San Francisco; Studer, J. and Ansal, A., 2004. Belediyeler icin Sismik Mikrobolgeleme El Kitabi, Arastirma Raporu, Afet Isleri Genel Mudurlugu, Bayindirlik ve Iskan Bakanligi, Afet Risk Yonetimi Dunya Enstitusu]. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: seismic microzonation; site response; seismic hazard; spectral amplification; Zeytinburnu; Engineering; Geology